Analisis Potensi Pemanenan Air Hujan Dengan Teknik Rainwater Harvesting Untuk Kebutuhan Domestik - Cut Suciatina Silvia; Meylis Safriani (Universitas Teuku Umar, 2018)
Gampong Leuhan is one of the areas in West Aceh district where most of the people still use ground water as a source of daily necessities. Some people have used artesian wells or drilled wells, but if we look at the cost of manufacture is very expensive. If more use of ground water from the drilling system, then will be inflict an impact of land subsidence. with these conditions, to overcome the problem of the need for clean water and lack of water for people's lives, it needs more effective and efficient system. One of proses is to make rainwater harvesting system from the rooftop of the building/housing by maximizing high rainfall. Field survey indicate building area in Gampong Leuhan already in good condition and livable with dominant house rooftop made of zinc, that this condition will be very maximum in rainwater harvesting process. The analysis of rain harvesting potential in Gampong Leuhan shows 887.892 liters/day, with average rainwater harvesting potential for each house is 862,031 liters/day. The ratio between the total amount of water harvested is 887.892 liters/day with the total use of water for the needs of the people of Gampong Leuhan amounted to 482.346,90 liters/day, indicates that with rainwater harvesting techniques will be sufficient and able to become one of the alternatives in the supply of clean water. Keywords: Clean water, Rainfall, Potential of rain water, Rainwater harvesting.